Faktor-Faktor yang Mempengaruhi Kemiskinan Absolut di Kabupaten Barito Kuala - Meilinda, Herly (PPJP ULM, 2018)
This research was conducted to analyze the factors that influence absolutepoverty in Barito Kuala Regency. One of the causes of the still high population is poordue to the rapid population growth. The still high number of poor people is indicated bya large number of poor people, economic growth, high unemployment rate, and low levelof education. This research is located in Barito Kuala District, as well as data source used issecondary data consisting of time series data during the period 2004 to 2015, in whichthe data is analyzed using multiple linear regression models. To find out whethereconomic growth, open unemployment rate, population growth, and education levelaffect the number of poor people in Barito Kuala District. The results of this study indicate that the variables of the open unemploymentrate, economic growth, and education level do not significantly affect the number of poorpeople, while population growth significantly influences the number of poor people.